nick_sun wrote:

Guys, please explain how you solve these equations.

**Quote:**

(3r + 2 - s)(4r +9 - s) = 0

(4r - 6 - s)(3r + 2 - s) = 0

you don't have to solve them:

when you know that (3r + 2 - s)(4r +9 - s) = 0

either (3r + 2 - s) = 0 or (4r +9 - s) = 0

but we can't know which one ! (think on (x-2)(x-3) = 0 , either x = 2 or x

= 3 but you can't say for sure which one)

from statement 2 - we know that (4r - 6 - s)(3r + 2 - s) = 0

either (3r + 2 - s) = 0 or (4r - 6 - s) = 0 (same problem as statement 1)

if both statements are correct & using both statements (choice C) we can

say that 3r + 2 - s = 0

if it was not equal 0 then 4r - 6 - s had to be equal to 4r + 9 - s

but we know its not equal !!! (look at -6,9)

hence the the answer is (C)